2023
DOI: 10.3390/su15097202
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on Extreme Climate Indices in Türkiye Driven by High-Resolution Downscaled CMIP6 Climate Models

Abstract: In this study, the latest release of all available Coupled Model Intercomparison Project Phase 6 (CMIP6) climate models with two future scenarios of Shared Socio-Economic Pathways, SSP2-4.5 and SSP5-8.5, over the period 2015–2100 are utilized in diagnosing climate extremes in Türkiye. Coarse-resolution climate models were downscaled to a 0.1° × 0.1° (~9 km) spatial resolution using the European Centre for Medium-Range Weather Forecasts Reanalysis 5-Land (ERA5-Land) dataset based on three types of quantile mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…It is projected that climate change will be one of these major risks and exacerbate the adverse weather or extreme weather impacts by altering the magnitude and/or frequency of the events. Gumus et al [43] have reported that there is an increasing trend in the frequency and intensity of extreme rainfall events. Similarly, there is an expected increase in the frequency of temperature extremes, such as the coldest, warmest, and mean daily maximum temperature, across all regions of Türkiye.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is projected that climate change will be one of these major risks and exacerbate the adverse weather or extreme weather impacts by altering the magnitude and/or frequency of the events. Gumus et al [43] have reported that there is an increasing trend in the frequency and intensity of extreme rainfall events. Similarly, there is an expected increase in the frequency of temperature extremes, such as the coldest, warmest, and mean daily maximum temperature, across all regions of Türkiye.…”
Section: Discussionmentioning
confidence: 99%
“…When the historical and future performance of Formwork (F) activity for January 30th are compared, the increasing workability values can be seen, especially for the coastal, eastern, and southeastern regions (Figure 3c,d). It is also possible to say that the dominant impact factor of the activity for the selected day is Tmax0 • C since an increasing minimum temperature is prominent in the future for the entirety of Türkiye [43]. Similar to Earthworks, summer workability is stationary (Figure 4c,d).…”
Section: Spatial Variation In Activity Performances Over Türkiyementioning
confidence: 95%
See 3 more Smart Citations